Global, regional, and national burden of myocarditis in children aged 0–14 years, 1990–2021: analysis for the global burden of disease study 2021 - Zhang, Yi-Dong; Chen, Nuo; Wang, Qiao-Yu; Li, Hao; Zhang, Song-Yue; Xia, Tian-He; He, Yue-E.; Rong, Xing; Wu, Ting-Ting; Wu, Rong-Zhou (Frontiers in Public Health, 2024)
ObjectiveThere are limited epidemiological data on myocarditis in children aged 0–14 years. This study aims to investigate the trends in incidence, mortality, disability-adjusted life years (DALYs), and corresponding estimated annual percentage change (EAPC) of myocarditis in children aged 0–14 years from 1990 to 2021.MethodsWe utilized the 2021 Global Burden of Disease, Injuries, and Risk Factors Study (GBD) analytical tools to examine the incidence, mortality, and DALYs of myocarditis in children aged 0–14 years, considering factors such as age, sex, region, sociodemographic index (SDI), and data from 204 countries or regions.ResultsIn 2021, a total of 155.45/1000 people cases of myocarditis were reported globally in children. The cases of myocarditis in children increased from 143.80/1000 people (95% uncertainty interval [UI], 93.13–214.67) in 1990 to 155.45/1000 people (95% UI, 100.31–232.31) in 2021, increasing by 8.1% (95% UI, 6.04–9.73%). Over 30 years, the global incidence rate decreased from 8.27 (95% UI, 5.35–12.34) to 7.73 (95% UI, 4.99–11.55) per 100,000 population. The myocarditis-associated mortality rate decreased from 0.36 (95% UI, 0.25–0.51) to 0.13 (95% UI, 0.10–0.16) per 100,000 population. In 2021, the highest incidence of myocarditis in children occurred in High SDI regions. Regionally, High-income Asia Pacific had the greatest increase in incidence (EAPC, 0.25; 95% CI, 0.22–0.28). Japan had the highest incidence rate of myocarditis in children, while Haiti reported the highest myocarditis-associated mortality rate and DALYs rate. Globally, environmental/occupational risk, nonoptimal temperature, high temperature, and low temperature were key risk factors for myocarditis-associated mortality in children.ConclusionBetween 1990 and 2021, myocarditis in children saw declining mortality and DALYs but rising incidence, especially in males. Children under 1 year face higher mortality and DALY rates despite lower incidence, stressing early diagnosis. High SDI regions report higher incidence but lower mortality, while low SDI areas need standardized treatment. Japan had the highest 2021 incidence, and China had the most deaths. Underscoring the urgency for enhanced medical resources, comprehensive research into the disease’s etiology, and improved prevention strategies.